Impact of sleep behavior on glycemic control in type 1 diabetes: the role of social jetlag. Issue 5 (November 2016) - Larcher, Sandra; Gauchez, Anne-Sophie; Lablanche, Sandrine; Pépin, Jean-Louis; Benhamou, Pierre-Yves; Borel, Anne-Laure
Abstract : Background: Sleep behavior is changing toward shorter sleep duration and a later chronotype. It results in a sleep debt that is acquitted on work-free days, inducing a small but recurrent sleep misalignment each week, referred to as "social jetlag". These sleep habits could affect health through misalignment with circadian rhythms. Objectives: The primary objective is to address the impact of sleep behavior on glycemic control, assessed by HbA1c, in patients with type 1 diabetes, independently of other lifestyle or sleep-related factors. The secondary objective is to address whether circadian phase affects glycemic control. Design: In total, 80 adult patients with type 1 diabetes (46% female) were included in a clinical cohort study. Methods: Sleep behavior was addressed objectively by a 7-day actimetry, lifestyle by questionnaires, sleep breathing disorders by nocturnal oximetry and circadian phase by dim light melatonin onset (DLMO). Results: Univariate analyses showed that chronotype ( r  = 0.23, P  = 0.042) and social jetlag ( r  = 0.30, P  = 0.008) were significantly associated with HbA1c. In multivariable analysis, social jetlag was the only sleep habit independently associated with HbA1c (β = 0.012 (0.006; 0.017), P  < 0.001). HbA1c was lower in patients with a social jetlag below versus above the median (7.7% (7.1–8.7) and 8.7% (7.6–9.8), P  = 0.011). DLMO was not associated with HbA1c. However, the later the DLMO, the worse the sleep efficiency ( r  = −0.41, P  < 0.001) and fragmentation index ( r  = 0.35, P  = 0.005). Conclusions: Social jetlag, a small but recurrent circadian misalignment, is associated with worse glycemic control in type 1 diabetes, whereas circadian phase is not. Further intervention studies should address the potential improvement of glycemic control by correcting social jetlag.